Resonance-enhanced multiphoton ionization spectroscopy oflaser-ablated copper atoms - Andrejeva, Anna; Harris, Joe P.; Wright, Timothy G. (Elsevier, 2014)
Resonance-enhanced multiphoton ionization (REMPI) spectra of laser-ablated copper atoms entrainedin a supersonic free jet expansion are reported. Depending on the ionization scheme employed, andthe conditions under which the copper atoms are produced, very different spectra are produced, whichare discussed. In some circumstances, high proportions of metastable atoms survive the ablation andexpansion process and are clearly seen in the spectra. The spectroscopic transitions for the observedlines are identified, and it is noted that some caution is merited in the assumption that only ground statecopper atoms are present following laser ablation.